Nanostructured Lipid Carrier (NLC) Based Gel as Patchouli Oil Delivery : Physical Characteristic and In Vivo Skin Irritation Test - Mayangsari, Fransisca Dita; Aditya Sindu Sakti; Merry Anggelya Mentari (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Patchouli oil (PO) contained patchoulol, which has antioxidant activity, making it a valuable ingredient in anti-aging products. However, this oil is volatile and chemically unstable. Therefore, it needs to be formulated into a Nanostructured Lipid Carriers based gel (NBG). This study aims to observe the effect of PO’s concentration on the physical characteristics and skin irritation of NBG preparations. NBG consists of 50% NLC and 50% gel. There are three formulas observed in this study, namely NBG-0 (0% PO), NBG-2 (2% PO), NBG-4 (4% PO). NLC prepared using the High Shear Homogenization method. Based on the physical characteristics test, it is known that all formulas have differences in the aroma aspect, where NBG-0 odorless, while NBG-2 and NBG-4 have a patchouli scent. All formula do not have differences in color and consistency. All formula have a pH in the range of 5.92 - 6.21. Statistically, increasing the concentration of PO decreases the pH of NBG. The three formulas have a viscosity in the range of 4.493 - 9.880 cP. Statistically, viscosity of NBG increasased by increasing concentration of PO. Based on in vivo skin irritation tests using white mice, it is known that all formulas have the same IIP (Primary Irritation Index) value. Based on the study, it can be concluded that the concentration of PO (0%, 2%, 4%) affects the aroma, pH and viscosity aspects but does not affect the color and consistency of NBG. Increasing the PO concentration in NBG up to 4% did not cause skin irritation.